TANGGUNGJAWAB NAZHIR KOPERASI SYARIAH SEBAGAI LKS PWU DALAM PENGELOLAAN WAKAF UANG MELALUI APLIKASI FINTECH - Siti Nurhayati, Nurjamil (Fakultas Hukum Universitas Komputer Indonesia, 2020)
This research was conducted to determine the form of Islamic cooperative nazhir responsibilities as PWU LKS in the management of waqf especially for a loss case in the management of waqf money. The study was a qualitative analytical study with a normative juridical approach. Data obtained through library research and field research and then analyzed qualitatively. This research was conducted in the city of Bandung, in this case the object of the study was the Sharia Cooperative that had been designated as a nazhir waqf for money by the Indonesian Waqf Board. The study concluded that if problems in the management of waqf money such as the occurrence of problematic financing or NPF, occured due to Nazir errors, either due to deliberate or negligence and / or due to non-consideration of the principle of prudence, then Nazir can be held liable according to the responsibility based on the error (based on error) on fault). This is regulated in the Civil Code (hereinafter abbreviated as the Civil Code) specifically contained in Articles 1365, 1366 and 1367. If some provisions relating to the principle of responsibility based on errors can be proven, Nazirs were required to compensate and return the endowment funds. Conversely, if the problems occured are not due to Nazir's fault, Nazir cannot be held accountable, both morally and legally. Compensation for wakaf assets shall be borne by other parties who cooperate with Nazir as stipulations regarding defaults or acts against the law stipulated in the Civil Registry Keywords: Responsibility, Nazhir Wakaf Money, PWU LKS, Fintech